Are countries' self-reported assessments of their capacity for infectious disease control reliable? Associations among countries' self-reported international health regulation 2005 capacity assessments and infectious disease control outcomes - Feng-Jen Tsai; Mathuros Tipayamongkholgul (BMC, 2020)
Abstract Background This study aimed to evaluate associations among countries' self-reported International Health Regulation 2005 (IHR 2005) capacity assessments and infectious disease control outcomes. Methods Countries' self-reported assessments implemented by percentages as IHR Monitoring Tools (IHRMT) in 2016 and 2017 were used to represent national capacity regarding infectious disease control. WHO Disease Outbreak News and matched diseases reports on ProMED-mail were collected in 2016 to represent disease control outcomes of countries. Disease control outcomes were divided in good, normal and bad groups based on the development of outbreaks listed in the reports. The Human Development Index (HDI), density of physicians and nurses, health expenditure, number of arrivals of international tourists were also collected for control. Chi-square test and logistic regression were applied for analysis. Results A total of 907 cases occurred in 92 countries. For all diseases, cases occurring in high international travel volume countries presented twice the risk of having a bad disease control outcomes than cases occurring in low international travel volume countries (OR = 2.19 for IHR 2016, OR = 2.97 for IHR 2017). Cases occurring in low IHR average score countries had significant higher risk (OR = 7.83 for IHR 2016 and OR = 2.23 for IHR 2017) of having a bad disease control outcomes than countries with high IHR average scores. For only human diseases, cases occurring in high international travel volume countries presented twice the risk of having a bad disease control outcomes than cases occurring in low international travel volume countries for IHR 2017 (OR = 2.79). Cases occurring in low IHR average score countries had significant higher risk (OR = 11.16 for IHR 2016 and OR = 3.45 for IHR 2017) of having a bad disease control outcomes than countries with high IHR average scores. The HDI, health workforce density and total health expenditure were all positively associated with disease control outcomes. Conclusions Countries' self-reported infectious disease control capacities positively correlated with their disease control outcomes. While the self-reported IHR scores were accountable to some degree, this approach was useful for understanding global capacity in infectious disease control and in allocating resources for future preparedness.